A citation-analysis of economic research institutes - Rolf Ketzler; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2012)
The citation analysis of the research output of the German economic research institutes presented here is based on publications in peer-reviewed journals listed in the Social Science Citation Index for the 2000-2009 period. The novel feature of the paper is that a count data model quantifies the determinants of citation success and simulates their citation potential. Among the determinants of the number of cites the quality of the publication outlet exhibits a strong positive effect. The same effect has the number of the published pages, but journals with size limits also yield more cites. Field journals get fewer citations in comparison to general journals. Controlling for journal quality, the number of co-authors of a paper has no effect, but it is positive when co-authors are located outside the own institution. We find that the potential citations predicted by our best model lead to different rankings across the institutes than current citations indicating structural change.
Keywords: A11; C53; I23; L31; 330; citation analysis; rankings; scientometrics; publication analysis; economic research institutes